PERANCANGAN ANIMASI PENDEK SEBAGAI KAMPANYE MENEBAR HARAPAN DITENGAH WABAH COVID-19 - anas, Afdal (Narada : Jurnal Desain dan Seni, 2022)
This design aims to make animated short as a media for a campaign to spread hope in the midst of the Covid-19 pandemic. The author takes this theme because the author sees that many people have started to ignore this pandemic. A campaign of dissemination like this the writer considers important, because the author believes that ignoring a pandemic like this is something that should not be allowed, this is because with this kind of omission, the opportunity for an increase in cases of the Covid-19 pandemic will increase. The author then tried to present this design to spread hope and give hope to people who have begun to ignore the Covid-19 pandemic. By making this animated short, the author tries to touch the psychological side of the Indonesian people in general and the people of Makassar city in particular to start caring about and not being indifferent to this Covid-19 pandemic.